Estimation of creep strain and creep failure of a glass reinforced plastic by semi-analytical methods and 3D numerical simulations. (October 2015) - Lavergne, F.; Sab, K.; Sanahuja, J.; Bornert, M.; Toulemonde, C.
Highlights: Aging creep of a glass fiber reinforced PVC is successfully modeled by homogenization. The Mori–Tanaka scheme and 3D numerical simulations are successfully compared. An estimate of creep failure related to the strength of glass fibers is proposed. The influence of the volume fraction and the length of fibers are investigated. Abstract: Glass reinforced plastics based on polyvinyl chloride (PVC) is a material of choice for construction applications, such as pipes. The lifetime of pipes may be limited by creep failure and polymers exhibit a viscoelastic response that depends on the time of loading. In this paper, homogenization methods are designed to upscale the viscoelastic properties of a composite material made of chopped glass fibers with random orientations and PVC. The estimates of the Mori–Tanaka scheme and 3D numerical computations for creep strains and creep failure are compared, validating the Mori–Tanaka model as a practical tool to predict the effect of fiber length and volume fraction of fibers on creep strain and creep failure. In particular, it appears that, for a given creep load, the lifetime of the material is increased if the volume fraction of fibers increases or if the length of fibers decreases, as long as the failure mode is fiber breakage.